Pengaruh Profitabilitas, Likuiditas, dan Free Cash Flow Terhadap Dividen Tunai dan Dampaknya Terhadap Nilai Perusahaan (Studi Pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia) - Yunita Sahputri; Islahuddin Islahuddin; Muhammad Arfan (Program Magister Akuntansi Unsyiah, 2016)
This research is aimed to examine the effect of profitability, liquidity, and free cash flow to cash dividend and the effect of cash dividend on firm value. The population used in this research were banking companies listed in Indonesia Stock Exchange during the period of 2009 to 2011. Methods of data analysis performed in this study using path analysis test. This research gave results that profitability, liquidity, and free cash flow simultaneously or partially had positive effect on cash dividends, and cash dividends has positive effect on firm value.KEYWORDS : Profitability, Liquidity, Free Cash Flow, Cash Dividend, Firm Value